2019
DOI: 10.3389/fpsyg.2019.02697
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Motivation in Developed Economies With Secular Stagnation

Abstract: In recent years, the slow pace of economic growth, high indebtedness, and high unemployment registered in most developed economies since 2009 have revived the debate over the “secular stagnation hypothesis” first formulated by the Keynesian economist Alvin Hansen in 1938. This return of the secular stagnation hypothesis occurred in November 2013, when Lawrence Summers postulated that the global economy was facing a scenario of low growth, low inflation, and a reduction in GDP per capita due to a chronic insuff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, the current college entrepreneurship education system in China is imperfect, and it has no practical application value for cultivating undergraduates’ sense of entrepreneurial responsibility and improving their innovative ability. Relevant research showed that the core problem faced by current college students was not only the ability to take on financial risks but also the psychological responsibility to withstand setbacks ( Obschonka et al, 2018 ). Although college students are keen on entrepreneurship, they lack self-awareness by blindly following the trend of entrepreneurship and using entrepreneurship as a means of comparison and competition, regardless of whether they are suitable for entrepreneurship or whether they are mature enough for entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%
“…However, the current college entrepreneurship education system in China is imperfect, and it has no practical application value for cultivating undergraduates’ sense of entrepreneurial responsibility and improving their innovative ability. Relevant research showed that the core problem faced by current college students was not only the ability to take on financial risks but also the psychological responsibility to withstand setbacks ( Obschonka et al, 2018 ). Although college students are keen on entrepreneurship, they lack self-awareness by blindly following the trend of entrepreneurship and using entrepreneurship as a means of comparison and competition, regardless of whether they are suitable for entrepreneurship or whether they are mature enough for entrepreneurship.…”
Section: Introductionmentioning
confidence: 99%